Common Fixed Points for Two Mappings with Implicit-Linear Contractions on Partially Ordered 2-Metric Spaces (Communications in Mathematical Research, 2019)
In this paper, we introduce a new class ${\cal U}$ of 3-dimensional real functions, use ${\cal U}$ and a 2-dimensional real function $φ$ to construct a new implicit-linear contractive condition and obtain some existence theorems of common fixed points for two mappings on partially ordered 2-metric spaces and give a sufficient condition under which there exists a unique common fixed point. The obtained results well generalize and improve the corresponding conclusions in references.